SENGKETA SERTIFIKAT HAK MILIK GANDA DALAM PERSPEKTIF TEORI TUJUAN HUKUM - Pranoto, Hadi (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Related to this research, the object of philosophical thinking is the role of the land office when facing multiple SHM disputes in the perspective of the legal objective theory. This problem originated from Allan Tjipta Rahardja who owned a plot of land covering an area of 33,170 M2 based on SHM No. 12/Kelurahan Gunung Anyar Tambak, Rungkut District, Surabaya City. Physical control over the parcels of land since it was bought by Allan Tjipta Rahardja is in his possession, and as long as his possession has never been disputed by anyone. Then in early 2008 the land belonging to Allan Tjipta Rahardja was seized and physically controlled by Haji Musofaini, resulting in a dispute over ownership of the land rights between Allan Tjipta Rahardja and Haji Musofaini. SHM No. 12/Kelurahan Gunung Anyar Tambak owned by Allan Tjipta Rahardja is listed in the land book No. 9722 / 84.85 Date 18-February-1985. All this time, an inspection has been carried out and is in accordance with the Land Book in Surabaya City Land Office II, recorded in a clean condition of all burdens, so that it can be used as collateral goods. No. 12/Kelurahan Gunung Anyar Tambak. The research method use normative legal research method, namely a library research approach that is focused by conducting an applied study of a rule or a norm on positive law in relation to the substance of this paper. The results showed that in a case of multiple SHM disputes, the Land Office was passive, so the disputing parties had to